Demographic variables, clinical aspects, and medicolegal implications in a population of patients with adjustment disorder - Anastasia A; Colletti C; Cuoco V; Quartini A; Urso S; Rinaldi R; Bersani G (Neuropsychiatric Disease and Treatment)
Annalisa Anastasia,1 Chiara Colletti,1 Valentina Cuoco,1 Adele Quartini,1 Stefania Urso,2 Raffaella Rinaldi,2 Giuseppe Bersani1 1Department of Medical-Surgical Sciences and Biotechnologies, Faculty of Pharmacy and Medicine, Sapienza University of Rome, 2Department of Anatomical, Istological, Forensic and Locomotor System Sciences, Sapienza University of Rome, Rome, Italy Introduction: Although adjustment disorder (AD) is considered as residual diagnosis and receives little attention in research, it plays an important role in clinical practice and also assumes an increasingly important role in the field of legal medicine, where the majority of diagnostic frameworks (eg, mobbing) often refer to AD. Our study aimed to look for specific stressor differences among demographic and clinical variables in a naturalistic setting of patients with AD.Methods: A restrospective statistical analysis of the data of patients diagnosed with AD from November 2009 to September 2012, identified via manual search from the archive of the outpatient setting at the University Unit of Psychiatry “A. Fiorini” Hospital, Terracina (Latina, Italy), was performed.Results: The sample consisted of 93 patients (46 males and 47 females), aged between 26 and 85, with medium–high educational level who were mainly employed. In most cases (54.80%), a diagnosis of AD with mixed anxiety and depressed mood was made. In all, 72% of the sample reported a negative family history for psychiatric disorders. In 22.60%, a previous history of psychopathology, especially mood disorders (76.19%), was reported. The main stressors linked to the development of AD were represented by working problems (32.30%), family problems (23.70%), and/or somatic disease (22.60%) with significant differences with respect to age and sex. Half of the patients were subjected to a single first examination; 24.47% requested a copy of medical records.Conclusion: Confirming previous data from previous reports, our results suggest that AD may have a distinct profile in demographic and clinical terms. Increased scientific attention is hoped, particularly focused on addressing a better definition of diagnostic criteria, whose correctness and accuracy are critical, especially in situations with medicolegal implications. Keywords: adjustment disorder, diagnostic criteria, stressor, mobbing, medicolegal